Fashion companies in Spain and the SDGs How do young people perceive their comunication? - Jordá Rodríguez, Aurora; Garcia Ortega, Beatriz (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The exercise carried out by the students of Competitiveness and Innovation in the company, of the Degree in Industrial Organization Engineer, is analyzed with respect to communication strategies in relation to the Sustainable Development Goals (SDG). The objective is to assess the selected companies through a relationship table and determine which SDGs whose compliance they communicate. The result is that the most used SDGs are: 5 Gender Equality, 12 Responsible Production and Consumption, and 13 Climate Action. It is concluded that different companies highlight different SDGs, which constitutes an important learning strategy on corporate communication.